Wohlgemuth was right: Distracting attention from the adapting stimulus does not decrease the motion after-effect - Morgan, Michael J. (2011)
We determined whether distracting the observer’s attention from an adapting stimulus could decrease the motion after-effect. Unlike previous studies we used a relatively bias-free 2AFC procedure to measure the strength of adaptation. The strength of motion adaptation was measured by the effects of a moving grating on the contrast discrimination (T vs. C) function for gratings moving in the same or opposite direction. As in previous reports, the effect of adaptation was to move the T vs. C function upwards and right-wards, consistent with an increase in the C50 (semi-saturation) response in the transduction function of the neural mechanism underlying the discrimination. On the other hand, manipulating the attentional load of a distracting task during adaptation had no consistent effect on contrast discrimination, including the absolute detection threshold. It is suggested that previous reported effects of attentional load on adaptation may have depended on response bias, rather than changes in sensitivity.